Por amor y coraje mujeres en movimientos urbanos de la ciudad de México - Massolo, Alejandra; Project Muse. (Colegio de Mexico, Programa Interdisciplinario de Estudios de la Mujer, 1992)
"Compelling exploratory investigation of women settlers in poor neighborhoods and their participation in social struggles during 1970s. Contends that although women were often the heart of social movements, their role has seldom been studied. Provides basic historical and theoretical/feminist frameworks. Mostly discusses life histories of four women and their recollections of popular struggles in three central and peripheral neighborhoods"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. 401-418).
Description based on print version record.
Keywords: Social movements -- Mexico -- Mexico City; Community development -- Mexico -- Mexico City; Women in community development -- Mexico -- Mexico City; Electronic books